The Alar Equalization Suture for Nasal Tip Refinement. Issue 3 (28th June 2022) - Savetsky, Ira L.; Hamilton, Kristy L.; Avashia, Yash J.; Rohrich, Rod J.
Abstract : Summary: Anatomic subtleties of the nasal tip have a dramatic impact on the overall appearance of the nose. Creation of the ideal nasal tip in rhinoplasty requires straight lower lateral cartilages, everted lateral crura, a higher caudal edge of the lower lateral cartilages relative to the cephalic margin, and a diamond-shaped tip. In this article, the authors describe the alar equalization suture, a suture technique that further refines nasal tip shaping after traditional maneuvers have been performed.